Hubungan Antara Self-Efficacy dengan Pengambilan Keputusan Karier pada Mahasiswa Tingkat Akhir Fakultas Psikologi: (Studi Kasus Pada Universitas Di Jakarta Barat) - Ruth Imelda Kurniasari; Agoes Dariyo; Rita Markus Idulfilastri (Journal An-Nafs: Kajian Penelitian Psikologi, 2018)
Bandura (1997) says that self-efficacy is an individual's belief in his ability that affects the individual's way of reacting to certain situations and conditions. According to Gati, Krausz and Osipow (1996) suggested career decision-making refers to "ideal career decision maker". The statement means the process by which the individual is aware of a need to make a career decision, be able to make it happen, and be able to make the right decision by using the right process and best suited to the individual's goals. The purpose of this study is to determine the relationship between self-efficacy and career decision making at the final grade students at the Faculty of Psychology (Case Study at University In West Jakarta). Researchers obtained data of 214 subjects of final level of faculty of psychology at 5 universities in West Jakarta, with male gender amounted to 46 students and female gender amounted to 168 students. This study uses convenience sampling technique, data collection in this study using self-efficacy questionnaires, and questionnaires career decision-making difficulties. The result of data analysis using parametric technique, that is pearson correlation. Based on data analysis, there is a significant negative relationship between self-efficacy and career decision making (r = -0.409, p = 0,000 <0.01)